Brief Historiography of Islamic Education for the Indigenous Muslim Minority in Singapore - Othman, Abdullah; Yusof, Abdullah (Online Journal of Research in Islamic Studies, 2016)
The formal and informal Islamic education available in Singapore has not factored unfortunately, the need to educate the local Muslims on the historiography of Islamic Education. More so, the conventional educational system has for years and persisted until now, not regarded this body of knowledge and information as important or relevant for national heritage and identity or for social and cultural developments. A good appreciation of the historiography of Islamic education in Singapore would be paramount, especially for individuals who assumed leadership roles, policy setters and decision-makers among the Muslims and the designated non-Muslim office bearers. It would be unfortunate and problematic, if the subject matter remained ambiguously or worse erroneously understood, by these key players because efforts towards defining, correcting, improving and refining matters in relation to Islamic education within Singapore context, should be based on proper understanding and analysis of the history, ideas, efforts and legacy of the early Muslims, the British colonialist, the government and related agencies, important institutions and personalities that influenced the Islamic education landscape until today.